2018
DOI: 10.7196/sajog.1290
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to cervical cancer screening uptake among rural women in South West Nigeria: A qualitative study

Abstract: RESEARCHBackground. Diverse barriers influence cervical cancer screening uptake among rural women. The study explored barriers related to the uptake of cervical cancer screening among rural men and women in 14 communities of Ado-Odo Ota, Ogun State, Nigeria. Objective. To inform the development of a cervical cancer screening model for use by rural women. Methods. A qualitative exploratory research design was used. Qualitative information was collected from purposively sampled 28 individuals (13 rural men and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 12 publications
4
17
0
Order By: Relevance
“…It becomes worrisome knowing that only 8.7% of all eligible women have been reached with opportunistic screening in Nigeria 26 . Such poor screening rate has been linked to a spectrum of factors; weak health system, poor awareness, low‐risk perception, sociocultural barriers, fear of positive result, poverty, and acceptability of available screening options 27–30 . Despite the emphasis on taking advantage of women's contact with the health system to provide CCS services, evidence indicates that such opportunities have been missed 28,31 …”
Section: Introductionmentioning
confidence: 99%
“…It becomes worrisome knowing that only 8.7% of all eligible women have been reached with opportunistic screening in Nigeria 26 . Such poor screening rate has been linked to a spectrum of factors; weak health system, poor awareness, low‐risk perception, sociocultural barriers, fear of positive result, poverty, and acceptability of available screening options 27–30 . Despite the emphasis on taking advantage of women's contact with the health system to provide CCS services, evidence indicates that such opportunities have been missed 28,31 …”
Section: Introductionmentioning
confidence: 99%
“…It is this normative perception of privilege or exclusiveness that causes men and women to feel uncomfortable with the perceived inappropriateness about interactions involving a woman’s sexual organs that are not specifically with her husband. In addition to the fear of being seen as promiscuous due to the nature of cervical cancer, women reported that these two cancers – and female health issues in general – were generally taboo topics that should not be discussed except in private ( Thomas et al, 2011 , Azaiza and Cohen, 2008 , Khan and Woolhead, 2015 , Khazir et al, 2019 , Bayrami et al, 2015 , Malhotra et al, 2016 , Lunsford et al, 2017 , Shaw et al, 2018 , Onyenwenyi and Mchunu, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Gender inequality was comprised of one second-level analytical theme in that men tended to have more power and receive more priority than women in their respective societies (Theme 2.1). Husbands were noted to be a key barrier (Theme 2.1.1) as women were often unable to decide to undergo breast or cervical screening by themselves and needed the approval of their husbands, who sometimes did not believe that screening was required ( Shirzadi et al, 2020 , Binka et al, 2019 , Onyenwenyi and Mchunu, 2018 , William et al, 2013 , Keshavarz et al, 2011 ). Even if husbands permitted their wives to attend screening, women reported that it was a requirement to be accompanied by them ( Baron-Epel et al, 2004 , Khazaee-pool et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations